Does AI Respect Patient Dignity? A Critical Examination of Ethics in Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare promises revolutionary advancements, from personalized medicine to enhanced diagnostic accuracy...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine